Quantification of the damage caused by Meloidogyne enterolobii in okra - Costa Silva, Edgard Henrique [UNESP]; Soares, Renato Silva [UNESP]; Borges, Heloisa Oliveira [UNESP]; Franco, Carolina Andrade [UNESP]; Braz, Leila Trevisan [UNESP]; Martins Soares, Pedro Luiz [UNESP] (Empresa Brasil Pesq Agropec, 2019)
The objective of this work was to estimate the damage caused by Meloidogyne enterolobii in okra (Abelmoschus esculentus) and to verify the reliability of the reproduction factor as a suitable measure for selecting resistant okra genotypes. Increasing populations of M. enterolobii - 0, 500, 1,500, 3,000, 5,000, and 7,000 eggs and second-stage juveniles (J(2)) per plant, - were evaluated, in a completely randomized design. The pathogen showed a parasitism pattern similar to that of M. incognita, causing a significant decrease in morphological and agronomic traits. The pathogen reproduction factor should be used in the selection of okra genotypes for tolerance to M. enterolobii, in populations above 3,000 eggs or J(2).
Keywords: Abelmoschus esculentus; reproduction factor; root-knot nematode; susceptible host